Association of p53 codon 72 polymorphisms with expression status of hormone receptors like ER, PR, and HER-2 in invasive ductal breast carcinoma in Bangladeshi women - Md. Zillur Rahman; Md. Jibran Alam; Amlan Bhattacharjee; Md. Azizur Rahman Riyaz; Fahmida Binta Wali; Inzamamul Ismail Shawon; Syeda Rumman Aktar Siddiqui; Laila Khaleda; Mohammad Al-Forkan (Bangabandhu Sheikh Mujib Medical University Journal)
Background: There is a lack of data on prevalent genetic factors among female breast cancer patients from Bangladesh. p53, a suppressor gene, is crucial in breast cancer’s aetiology. This study aimed to investigate the association between p53 codon 72 polymorphisms and invasive ductal breast carcinoma (IDC) in Bangladeshi women.